Investigating the Ability of the English Literature Department Students in English Poetry Reading Skill - Andi Hudriati; Najihuddin Sain (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
The objectives of this study are: (1) To know students’ ability in reading English Poetry. (2) To know the difficulties that the student find in reading English Poetry. The data was analyzed by using a quantitative descriptive method. The study data was collected by using some research instruments, such as reading test and interview. The data were tabulated into students’ average scores in five indicators and mean scores. Then, the authors explained the data descriptively. Based on the data findings, the students’ ability to read English Poetry was qualified as “poor”. This was indicated by the score in each part of the students were low, especially in facial expression and body language. Through this study, the authors aimed to help the student to learn how to read English Poetry, and the students hoped to increase their ability to read English Poetry.